2006
DOI: 10.1111/j.1439-0396.2006.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy intake and cold exposure on kinetics of plasma glucose metabolism in sheep

Abstract: An isotope dilution method using [U-(13)C]glucose injection was applied to determine the effects of dietary energy intake and cold exposure on plasma glucose metabolism in sheep. The sheep were assigned to two dietary treatments and were fed on diets containing either 100% or 160% of ME and both containing 150% of dietary crude protein intake for maintenance. The sheep were exposed from a thermoneutral environment (23 degrees C) to a cold environment (2-4 degrees C) for 5 days. The isotope dilution method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…Moreover, the Chinese herbal medicine might also produce impact to enhance plasma glucose kinetics due to its bioactive properties on hematopoiesis. Previous findings (Al‐Mamun, Sako, & Sano, ; Sano et al., ) reported an increased plasma GluTR in sheep during the cold exposure period, which is in accordance with our present result. When the animals are exposed to cold, the oxidation of nutritive substances in the body should increase to meet the increased heat requirement.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, the Chinese herbal medicine might also produce impact to enhance plasma glucose kinetics due to its bioactive properties on hematopoiesis. Previous findings (Al‐Mamun, Sako, & Sano, ; Sano et al., ) reported an increased plasma GluTR in sheep during the cold exposure period, which is in accordance with our present result. When the animals are exposed to cold, the oxidation of nutritive substances in the body should increase to meet the increased heat requirement.…”
Section: Discussionsupporting
confidence: 94%
“…Various studies have well verified that plasma glucose concentration was influenced by cold exposure in sheep (Sano, Sano et al, 2007) reported an increased plasma GluTR in sheep during the cold exposure period, which is in accordance with our present result. When the animals are exposed to cold, the oxidation of nutritive substances in the body should increase to meet the increased heat requirement.…”
Section: Plasma Glucose and Leucine Kineticssupporting
confidence: 93%
See 1 more Smart Citation
“…With its assumed low tannin content [66], the 100% MSM diet would have protected these amino acids from ruminal microbial degradation [98]. Indeed, an increase in glucose concentration may be due to more by-pass protein and increased availability of glucogenic amino acids for glucose synthesis [99]. Increased post-ruminal flow of glucogenic amino acids and lipogenic moieties results in improved muscle mass accretion [100].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results [26] noticed that there was an increasing in concentration of blood glucose due to more glucogenic amino acids available for gluconeogenesis, when the protein from leguminouse leaves was added in the diet. An increasing in glucose concentration occured due to more by-pass protein and increased availability of glucogenic amino acids for glucose synthesis [27]. When sheep fed Gliricidia sepium as protein sources feed was increased [28].…”
Section: Glucose Metabolismmentioning
confidence: 99%